The Role of the Regional Supervisory Council of Notaries in Maintaining the Integrity of the Notary Profession (Case Study in Demak Regency) - Riska Dwi Damayanti (Faculty of Law, Universitas Negeri Semarang, 2025)
This study examines the role of the Notary Regional Supervisory Council (MPWN) in maintaining the integrity of the notary profession, focusing on case studies in Demak Regency. The main objective of this study is to identify the challenges faced by MPWNs in enforcing the professional code of ethics among notaries and explore effective strategies to improve their supervisory capabilities. Using a qualitative research methodology with a juridical empirical approach, data were collected through structured interviews with elements of government, notaries, and academics, as well as document analysis and direct observation. The findings show significant barriers, including limited human resources, budget constraints, and lack of ethical awareness among notaries, that hinder effective oversight. In addition, this study highlights the need for better training programs, the implementation of electronic monitoring systems, and stronger collaboration with the Indonesian Notary Association (INI) to build a culture of professionalism. The conclusion emphasizes that strengthening the capacity of the MPWN and the ethics enforcement mechanism is very important to maintain public trust in the notary profession and ensure compliance with regulations, in this case the Law on the Notary Position and the Code of Ethics for the Notary Profession.